Group Guidance with the Value Clarification Technique to Enhance Empathy among Students Involved in Passive Bullying - Titin KS; Nur Fadhilah Umar; M. Amirullah; Nurfaidah Ardis (Universitas Muhammadiyah Metro, 2026)
Passive bullying involvement refers to indirect participation in bullying situations, such as remaining silent, laughing, implicitly supporting the aggressor, or failing to assist the victim. Although this behavior is often overlooked in schools, it may reinforce the continuation of bullying and reflect limited empathic sensitivity among students. This study aimed to examine the empathy levels of students involved in passive bullying and to evaluate the effectiveness of group counseling using the Value Clarification Technique in enhancing empathy among eighth-grade students at SMP IT Darul Fikri Makassar. A quantitative approach with a quasi-experimental pretest–posttest nonequivalent control group design was employed. Twenty-four students participated and were assigned to an experimental group and a control group. The experimental group received group counseling using the Value Clarification Technique, whereas the control group received lecture-based services. Data were collected using an empathy scale and a passive bullying scale and were analyzed using descriptive statistics, N-gain analysis, and an independent-samples t-test. The results showed that the experimental group achieved a greater increase in empathy than the control group. The experimental group obtained a mean N-gain score of 0.52, categorized as moderate, whereas the control group obtained a mean N-gain score of 0.06, categorized as low. The difference in empathy improvement between the two groups was statistically significant (p < .001). Improvements were observed across the dimensions of perspective taking, fantasy, empathic concern, and personal distress. These findings indicate that group counseling using the Value Clarification Technique effectively helps students reflect on the values of care, justice, social responsibility, and moral courage when responding to bullying situations. The intervention can therefore be used by school counselors as a preventive and remedial strategy to enhance empathy and promote prosocial responses to bullying in schools.